Cervical screening and health inequality in England in the 1990s. Issue 6 (1st June 2003) - Baker, D; Middleton, E
Abstract : Study objectives: To examine changing inequality in the coverage of cervical screening and its relation to organisational aspects of primary care and to inequality in cervical cancer incidence and mortality. Design: Retrospective time trends analysis (1991–2001) of screening coverage and cervical cancer incidence and mortality in England. Setting: The 99 district health authorities in England, as defined by 1999 boundaries were used to create a time series of incidence and mortality rates from cervical cancer per 100 000 population. A subset of 60 district health authorities were used to construct a time series of screening coverage data and GP and practice characteristics. Health authorities were categorised into one of three "deprivation" groups using the Townsend Deprivation Index. Participants: Women aged <35 and 35–64 were selected from health authority populations as the main focus of the study. Results: Cervical cancer screening coverage was consistently higher in affluent areas from 1991–9 but ratio rates of inequality between affluent and deprived health authorities narrowed over time. The increase in coverage in deprived areas was most closely associated with an increase in the number of practice nurses. Cervical cancer incidence and mortality rates were consistently higher in deprived health authorities, but inequality decreased. Screening coverage and cervical cancer rates were highly negatively correlated in deprived health authorities. Conclusion: A primary health care intervention such as an organised programme of cervical screening can contribute to reducing inequality in population health.